A Brief Overview of Gravity Wave Retrieval Techniques From Observations - Sakib, Md Nazmus; Yiğit, Erdal (Frontiers in Astronomy and Space Sciences, 2022)
Atmospheric gravity waves (GWs) are important in driving the middle and upper atmosphere dynamics on Earth. Here we provide a brief review of the most common techniques of retrieving gravity wave activity from observations. Retrieval of gravity wave activity from observations is a multi-step process. First, the background fields have to be removed as the retrieval of the wave activity highly depends on this. Second, since a broad spectrum of internal waves contribute to atmospheric fluctuations, the contribution of GWs has to be extracted carefully. We briefly discuss strengths, limitations/barriers and applications of each technique also. We outline some future research questions to improve the treatment of these wave extraction methods.